Making the financial system sustainable - Fisher, Paul G. (Paul Gregory) (Cambridge : Cambridge University Press, 2021)
The EU Action Plan on Financing Sustainable Growth is the most advanced and comprehensive policy agenda on sustainability in the world. But is it going in the right direction? Acting as a bridge between policy and academia, this up-to-date contribution to the global policy debate brings together some of the leading experts from the European Commission's High-Level Expert Group on Sustainable Finance, to discuss how the financial system needs to be reformed to promote sustainability. Finance has long been criticized for being short-term focused and concerned with maximizing returns to intermediaries, rather than with the interests of savers and borrowers. The financial system must now take into account environmental, social and governance considerations to support a sustainable economy and this volume offers new insights on the way forward. A must-read for anyone working on financial sector policy and sustainability.
Title from publisher's bibliographic system (viewed on 29 Oct 2020).
Keywords: elektronické knihy; electronic books; Finance -- Environmental aspects; Sustainable development; Economic development -- Environmental aspects; Capitalism -- Environmental aspects